PENGARUH PROMOSI DAN PERSEPSI HARGA TERHADAP LOYALITAS PELANGGAN DENGAN KEPUASAN PELANGGAN SEBAGAI MEDIASI DALAM MENGGUNAKAN JASA PADA YOPIE SALON KOTA PALANGKA RAYA - Zepanya Putri, Abigail; Sintani, Lelo; Budiman Bancin, John; Karuehni, Ina (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2026)
The increasingly intense competition in the beauty service industry requires companies to continuously build customer loyalty. This study aims to analyze the direct and indirect effects of promotion and price perception on customer loyalty, with customer satisfaction as a mediating variable at Yopie Salon Kota Palangka Raya. The research employed a quantitative explanatory approach involving 97 respondents selected through purposive sampling and analyzed using SEM-PLS (Structural Equation Modeling–Partial Least Squares). The findings indicate that promotion and price perception have positive and significant effects on both customer loyalty and customer satisfaction. However, customer satisfaction does not have a significant effect on customer loyalty and does not mediate the relationship between promotion and price perception and customer loyalty. These results suggest that customer loyalty is more directly influenced by promotion and price perception rather than through the mechanism of customer satisfaction.